Student Consumer Behavior Based on Financial Literacy, Lifestyle, and Self-Control: Theory of Planned Behavior Perspective - Sigit Hermawan; Nur Azizah; Akhmal Mulyadi; Sintha Wahyu Arista (IECON: International Economics and Business Conference, 2025)
Consumptive behavior is the behavior of consuming goods without prioritizing utility and needs, but rather fulfilling the desire to try new things to improve status, prestige, lifestyle, and personal satisfaction. Consumptive behavior includes impulsive buying, driven by emotions without rational thought, and wasteful behavior, which means spending money without prioritizing needs. This study adopts behavioral accounting theory with a focus on the Theory of Planned Behavior. This study is intended to examine the influence of financial literacy, lifestyle and self-control on the Consumer Behavior of Students of the Muhammadiyah University of Sidoarjo. This type of research uses a quantitative descriptive research method. The number of respondents in this study was 86 people. This study uses primary data questionnaires with a Likert scale processed using SmartPLS version 4 with validity tests and reliability tests. The results obtained are financial literacy, lifestyle and self-control are significant to consumer behavior. Financial literacy has been shown to have a positive impact, indicating that increased financial understanding can influence a person's consumption patterns. Lifestyle also has a positive and significant impact, reflecting the role of personal values and social identity in driving purchasing decisions. Furthermore, self-control plays a significant role with a positive influence on consumer behavior, indicating that the ability to manage internal impulses influences how individuals regulate consumption.